'They became my second family': Children's relational lives and relationship‐based practice in residential care in the Philippines. Issue 4 (26th April 2021) - Roche, Steven; Flynn, Catherine; Mendes, Philip
Abstract: Despite the widespread utilization of residential care in the Philippines, little is known about the lives and circumstances of children living within these contexts. In response, this article presents an analysis of children and young people's experiences of living in residential care, specifically focusing on their social networks, relationships and the relationship‐based practices of their caregivers. Drawing on 50 qualitative interviews with children and young people currently or previously living in residential care, as well as a range of social workers and programme staff, this study identifies the highly relational lives of children and young people who cite extensive and close relationships with residential care staff, peers and family. Analysis reveals that children conceptualize 'family' as embodied in their residential care programme, drawing attention to the collective support and security offered, while also detailing the role of their spirituality as an important support. Relationship‐based practices are utilized by caregivers who offer long‐term, emotionally close and stable relationships with children to support their well‐being. These findings highlight the centrality of relationship‐based interventions and the maintenance of children's relational lives as a core practice, offering insights into the development of practice in these settings.